(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Hypercholesterolemia is a hazardous disorder that increases the risk of coronary heart disease, heart attack, and stroke in persons with normal cholesterol levels. Nigella sativa (N. sativa) (Family Ranunculaceae) is a medicinal herb that is widely used worldwide. Numerous researchers have conducted extensive research on N. sativa, elucidating a broad range of its pharmacological actions, which may include antidiabetic, anticancer, immunomodulator, analgesic, antimicrobial, anti-inflammatory, spasmolytic, bronchodilator, hepatoprotective, renal protective, gastroprotective, and antioxidant properties. Thymoquinone (TQ) is a significant bioactive component found in the Nigella sativa (NS) black seeds. We examined the efficacy of TQ in the treatment of hypercholesterolemia in the current study. The TQ was docked with 20 proteins involved in cholesterol production. The docking data indicated that TQ had the greatest docking score with the majority of the target proteins and also exhibited a favourable interaction pattern with the target proteins. Thus, upon experimental validation, TQ may be an effective treatment for hypercholesterolemia.